Relationship between scrotal circumference and parameters of semen quality in male Guzerat Bulls from puberty to 36 months of age raised pasture in the savanah - Pérez-Osorio, Jair; Cardona-Álvarez, José Alberto; Gómez-León, Víctor Enrique; Otero-Arroyo, Rafael José (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The aim of this study was to investigate the association between the size of the scrotal circumference and physical characteristics of semen and sperm morphology, in 191 bulls of Guzerat breed. The bulls were divided by age in six groups from 12 to 36 months of age. Scrotal circumference and testicular measures were obtained by caliper and tape measure, according to the Brazilian College of Animal Reproduction' methodology. The animals with scrotal circumference 2 19cm, were subjected to semen collection using ejaculation by electro-stimulation. The evaluated semen characteristics were sperm motility and vigor, also assessments of sperm concentration and the presence of rounded cells. The correlation between scrotal circumference with sperm motility by age group, was positive (r = 0.94, P <0.005).The present study demonstrated that the presence of sperm with proximal cytoplasmic droplet, round cells in the ejaculation and defective sperm—head are the characteristics of objective assessment, which could be used for precocity selection of male sperm production. It can be concluded that the normality of sperm production in Guzerat breed, considering also all representative sperm production maturity process´ parameters, and the scrotal circumference above 30 cm, was reached over the age of 28 months.